(untitled) (International Journal of Engineering and Computer Science, 2021)
In modern years, there is a growing recognition of Virtual Reality(VR) in education and the logic behind this may be the distribution programs in various walks of life. With the minimal device framework, the developers can easily construct and organize applications that can be reachable from anywhere without the in-depth understanding of editing and managing 3D objects. In an intended design, Intelligent Virtual Assistant offers the opportunity for hospitality services to enhance the customer experience. The Virtual Assistant can give guests a more personalized experience with either a touch or a Virtual Agent, a custom kiosk, or a smartphone. If you are visiting for the first time and need to identify the local business and location on the map, this MIET Virtual Assistant will help you find them. This paper outlines the results of a project undertaken by the Meerut Institute of Engineering and Technology, AKTU, India, which aims to provide a purposeful hosting service in the VR area using amazon service which is known as AWS Sumerian . This project’s benefaction and shortcomings are explored.